Exploring the Role of Teaching Aids in Enhancing Physical Education for Schoolchildren: A Literature Review - Yurij Vaskov (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Physical education is an important aspect of school curriculum, and teaching aids play a crucial role in this process. The purpose of this study is to explore different approaches to defining teaching aids and their functions, as well as to identify sources for selecting them in the context of physical education for schoolchildren.